Analysis Of Shariah Economic Value Implementation And Its Implications On The Local Economy Study Of Bumdes In Gedung Harapan Village, Penawar Aji, Tulang Bawang - Muhammad Rizqi Muzakki; Didik Kusno Aji Nugroho; Ahmad Mukhlishin; Subandi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This research is motivated by the transformation of BUMDes Mekar Gemilang which revitalized its governance by integrating sharia values after experiencing failure in its savings and loan unit. This study aims to analyze the implementation of sharia values in the aspects of institutional governance, financing, business activities, and profit distribution at BUMDes Mekar Gemilang, as well as its implications for the local economy in Gedung Harapan Village, Penawar Aji District, Tulang Bawang Regency. This research employs a qualitative method with a descriptive approach. Data collection techniques were carried out through in-depth interviews, observation, and documentation. To ensure data validity, this study used source triangulation and technique triangulation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results show that: first, the implementation of sharia economic values at BUMDes Mekar Gemilang is comprehensively applied in the institutional aspect through the principles of trust (amanah) and deliberation (syura), in the financing aspect through a riba-free system with prudent capital management, in the business activity aspect through catfish farming that meets the halalan thayyiban principle, and in the profit distribution aspect through justice ('adl) by implementing an agreed profit-sharing system and a 5% social program for the poor. Second, the implementation of these sharia values has positive implications for the local economy, namely increasing community income through opportunities to buy and sell fresh fish, as well as absorbing part-time workers from economically disadvantaged groups through an inclusive rotating harvest system. This study concludes that the consistent application of sharia values in BUMDes management can create transparent, accountable, and socially just governance while making a real contribution to improving the economic welfare of the people of Gedung Harapan Village.